Concise Review: Chronic Myeloid Leukemia: Stem Cell Niche and Response to Pharmacologic Treatment. (8th February 2018) - Arrigoni, Elena; Del Re, Marzia; Galimberti, Sara; Restante, Giuliana; Rofi, Eleonora; Crucitta, Stefania; Baratè, Claudia; Petrini, Mario; Danesi, Romano; Di Paolo, Antonello
Abstract : Nowadays, more than 90% of patients affected by chronic myeloid leukemia (CML) survive with a good quality of life, thanks to the clinical efficacy of tyrosine kinase inhibitors (TKIs). Nevertheless, point mutations of the ABL1 pocket occurring during treatment may reduce binding of TKIs, being responsible of about 20% of cases of resistance among CML patients. In addition, the presence of leukemic stem cells (LSCs) represents the most important event in leukemia progression related to TKI resistance. LSCs express stem cell markers, including active efflux pumps and genetic and epigenetic alterations together with deregulated cell signaling pathways involved in self-renewal, such as Wnt/β-catenin, Notch, and Hedgehog. Moreover, the interaction with the bone marrow microenvironment, also known as hematopoietic niche, may influence the phenotype of surrounding cells, which evade mechanisms controlling cell proliferation and are less sensitive or frankly resistant to TKIs. This Review focuses on the role of LSCs and stem cell niche in relation to response to pharmacological treatments. A literature search from PubMed database was performed until April 30, 2017, and it has been analyzed according to keywords such as chronic myeloid leukemia, stem cell, leukemic stem cells, hematopoietic niche, tyrosine kinase inhibitors, and drug resistance.